The Allegorical Exegesis of Song of Songs by R. Tuviah ben 'Eliʽezer—Lekaḥ Tov, and Its Relation to Rashi's Commentary. Issue 1 (12th May 2015) - Jacobs, Jonathan
Abstract : This article examines three facets of R. Tuviah ben 'Eliʽezer's commentary, Lekaḥ tov, on Song of Songs: (a) his unique approach to allegorical interpretation; (b) his participation in Judeo-Christian polemics; and (c) the question of a connection between his commentary on Songs and Rashi's. R. Tuviah proposes to read the verses of Songs as simultaneously describing the past, the present, and the future of the Jewish nation, a type of reading that is extremely rare in rabbinic midrashim, which R. Tuviah adopts to create a systematic allegorical commentary. There are similarities between the interpretations of R. Tuviah and those of Rashi; while not numerous, all the same these two scholars were the first to propose a literal interpretation of Songs, they both engaged in similar Judeo-Christian polemic, and they interpreted Songs on the allegorical level in a similar fashion. These points of similarity support the possibility that Rashi was exposed to reports of R. Tuviah's commentary on Songs.